Perioperative Endocrine Therapy for Patients with Cushing's Syndrome Undergoing Retroperitoneal Laparoscopic Adrenalectomy - Xiaobo Cui; Lu Yang; Jianwei Li; Siyuan Bu; Qiang Wei; Zhenmei An; Tianyong Fan (International Journal of Endocrinology)
Objectives. To investigate the efficacy and safety of perioperative endocrine therapy (PET) for patients with Cushing’s syndrome (CS) undergoing retroperitoneal laparoscopic adrenalectomy (RLA). Methods. The novel, simplified PET modality of 82 patients who underwent RLA procedures for CS were studied. Clinical manifestations were observed for all patients on days 1 and 5 postoperatively, and clinical data, such as blood pressure (BP), levels of serum cortisol, adrenocorticotropin (ACTH), blood glucose, and electrolytes, were acquired and analyzed. Results. Supraphysiological doses of glucocorticoid were administered during the perioperative period, and the dosage was reduced gradually. In all 82 cases, the RLAs were performed successfully without any perioperative complication, such as steroid withdrawal symptoms. The patient’s symptoms and signs were improved quickly and safely during the hospital days. The serum cortisol and potassium levels were rather stable on days 1 and 5 postoperatively, and most were within the normal range. The clinical manifestations, serum levels of cortisol, ACTH, and potassium in most patients restored to normal gradually after several months (mean, 6.7 ± 1.2 months), except for one patient undergoing bilateral adrenalectomy. Conclusions. This perioperative endocrine therapy for patients with Cushing’s syndrome (mainly for adrenocortical adenoma) undergoing retro-laparoscopic adrenalectomy is both effective and safe.